Diversity and Distribution of Macrophytes in Fresh Waterbodies under Varying Degree of Anthropogenic Pressures - Slathia, Deepika; Thakur, Paress; Sheikh, Assadullah (Indian Forester, 2018)
The present paper communicates the ecological survey and distribution pattern of macrophytic diversity in some freshwater bodies of Billawar tehsil, Kathua district, J&K, India, located in the areas under varying degree of anthropogenic pressures. The study revealed the presence of 21 macrophytic species belonging to 19 genera and 15 families with highest diversity of emergent species (12 species) followed by rooted floating type and free floating type (03species each), submerged (02 species) and marginal (01 species) type. Among various water bodies selected for the present study, Stream A has shown maximum diversity (13 species) and Spring A minimum diversity (2 species). Family Polygonaceae and Apiaceae, among various families, have shown dominance followed by Apiaceae and Lemnaceae, respectively. Minimum percentage similarity of macrophytic diversity among different water bodies has been observed between ponds and springs (15.38%) and maximum between springs and streams (42.1%). The study recommends the urgent need for restoration, improvement and proper management of these water bodies in order to conserve the macrophytic diversity of the study area.